Pengaruh Sikap Siswa pada Pelajaran Matematika dan Kemandirian Belajar Siswa terhadap Prestasi Belajar Matematika - Yani Purnomo (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
This survey research with double regression analysis is aimed at 1) acknowledging the impacts of both student’s attitude on mathematics and student’s learning independence on mathematical learning achievement all together 2) acknowledging the impacts of student’s attitude on mathematical learning achievement 3) acknowledging the impact of student’s learning independence on mathematical learning achievement. The research was conducted at SMP Negeri 2 Taman Sari, Bogor, West Java in 2015/2016 by using simple random sampling with 72 respondents taken from the number of affordable population reach as many as 255 respondents. The instrument used is test on variables of mathematical learning achievement and questionnaire on variables of student’s attitude on mathematics and student’s learning independence and all instruments have been empirically validated. Hypothesis is conducted with F test and  test after the data fulfill in series of classic assumption test, i.e. normality test, linearity test and multicollinearity test. The research result show that 1) there are significant impacts of both student’s attitude on mathematics and student’s learning independence all together on mathematical learning achievement, 2) there are significant impacts of student’s attitude on mathematical learning achievement, 3) there are significant impacts of student’s learning independence on mathematical learning achievement.